2018
DOI: 10.1016/j.carbon.2017.10.087
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic control of surface plasmon-polaritons in a 3-layers graphene curved configuration

Abstract: In this paper, we utilize coupled mode theory (CMT) to model the coupling between surface plasmon-polaritons (SPPs) between multiple graphene sheets. By using the Stimulated Raman Adiabatic Passage (STIRAP) Quantum Control Technique, we propose a novel directional coupler based on SPPs evolution in three layers of graphene sheets in some curved configuration.Our calculated results show that the SPPs can be transferred efficiently from the input graphene sheet to the output graphene sheet, and the coupling is a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…The limitation comes from two aspects. One is the higher loss of SPPs in THz waveguides, comparing with the graphene SPPs waveguide coupler working at optical light region [24]. Typically, the propagation length of graphene SPPs can reach dozens of wavelength [34], which is slightly longer comparing with propagation length of SPPs in THz corrugated thin films structure (tens or dozens of wavelength [18]).…”
Section: Adiabatic Following Spps On Tri-layered Thin Film Couplermentioning
confidence: 99%
See 2 more Smart Citations
“…The limitation comes from two aspects. One is the higher loss of SPPs in THz waveguides, comparing with the graphene SPPs waveguide coupler working at optical light region [24]. Typically, the propagation length of graphene SPPs can reach dozens of wavelength [34], which is slightly longer comparing with propagation length of SPPs in THz corrugated thin films structure (tens or dozens of wavelength [18]).…”
Section: Adiabatic Following Spps On Tri-layered Thin Film Couplermentioning
confidence: 99%
“…Consequently, current THz SPPs-based devices are facing the problems of high-cost fabrication processing and narrow transferring band. Most recently, to overcome this shortcoming, a remarkable paper applied coherent quantum control (stimulated raman adiabatic passage, short for STIRAP) into transferring the SPPs on the graphene sheets [24]. STIRAP is the well-known three-level coherent quantum control, which completely transfers population from first state to third state, without any population remaining in intermediate state [25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is also a fundamental technique in quantum computation and quantum information processing, including superconductivity qubit [4,5], Bose-Einstein condensate [6], NV centers in diamond [7], quantum dots and quantum wells in semiconductor [8]. Another very important application of complete population transfer is to achieve power or intensity inversion in classical systems, which is widely used in waveguide coupler [9], wireless energy transfer [10], polarization optics [11] and electrons, surface plasmon polaritons in graphene system [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is a competitive two-dimensional material for active control due to its large conductivity range and ultrafast response [13,14]. Graphene-based metamaterials used as waveguides [15], switches [16] and sensors [17] have shown their potential in developing optical devices. Meanwhile, the THz devices integrated with graphene emerged the probability in active control: Li et al experimentally demonstrated an active diode for the THz waves consisting of a graphene-silicon hybrid film [18], and Kindness et al achieved active resonance frequency tuning of a THz metamaterial by integrating metal-coupled resonator arrays with electrically tunable graphene [19].…”
Section: Introductionmentioning
confidence: 99%